Uterine Artery Doppler Indices in the Various Causes of Abnormal Uterine Bleeding Confirmed with Histopathology - Saira Amin, Raham Bacha, Syed Muhammad Yousaf Farooq, Tayeba Ali, Mehreen Fatima, Sarwat Noreen, Iqra Manzoor, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: All disturbed pattern of bleeding which arises due to different reasons such as anovulation, pregnancy, uterine abnormalities and coagulopathies is termed as abnormal uterine bleeding (AUB). Abnormal uterine bleeding is present in many forms such as heavy bleeding, short menstrual cycle, excessive and heavy menstruation, uterine bleeding at irregular period, excessive and prolonged uterine bleeding. Abnormal uterine bleeding is mostly caused by benign findings such as endometrial hyperplasia or atrophy or benign polyps. Around 5–12% of Abnormal uterine bleeding results from Endometrial Cancer. Objective: Uterine artery Doppler indices in various causes of abnormal uterine bleeding confirmed with histopathology. Methodology: A Cross-sectional Analytical study was conducted at Shireen Ultrasound Clinic Peshawar, Pakistan. This study enrolled a purposive sample of 162 patients presenting with abnormal uterine bleeding with the age between 18 to 80 years. The examination was performed with Toshiba Nemio 20(Xario Prime with TVS Probe frequency range 7-14MHz) .The Resistive index(RI), Pulsatility index(PI), mean and standard deviation were calculated for the continuous variables. Results: A total of 162 patients were enrolled in our study. The mean age of patients was recorded 38±5 years. In this study, the histopathological findings were as follow, 8.6% adenomyosis,12.3% endometrial hyperplasia, 43.3% leiomyoma’s, 17.3% polyp, 2.5% endometrial carcinoma and 16% non-specific findings so the most common cause of abnormal uterine bleeding was leiomyoma’s with mean of Right Uterine artery (U-A) PI and RI was 3.33±1.23 and 0.83±0.03 respectively and left U-A PI and RI was 2.95±1.17 and 0.84±0.03 respectively while the least common cause was endometrial carcinoma with mean of Right U-A PI and RI was 2.54±1.08 and 0.52±0.01 respectively and of Left U-A PI and RI was 1.62±0.00 and 0.52±0.00 respectively. Conclusion: From our study we concluded that the uterine artery RI in endometrial carcinoma causing abnormal uterine bleeding is low and in benign condition like polyp, hyperplasia and fibroids is high. Keywords: Uterine bleeding, Carcinoma, Fibroids, Hyperplasia, Trans-vaginal ultrasound